Kearifan Lokal Dalam Adaptasi Penyelesaian Sengketa Tanah Akibat Ekspansi Investasi: Studi Kasus Pada Masyarakat Adat Di Merauke - Azis, Yuldiana Zesa; Rahail, Emiliana B. (Jurnal Restorative Justice, 2025)
Large-scale investment expansion in plantation development, food estates, and strategic infrastructure has intensified land conflicts between indigenous communities and investment actors in Merauke Regency. This article examines how the local wisdom of the Malind indigenous community functions as an adaptive strategy for resolving land disputes within an asymmetrical legal pluralism regime. Employing a qualitative socio-legal approach, this study is based on case studies conducted in Wasur, Rawa Biru, Sota, Erambu, and Yanggandur villages through in-depth interviews, participant observation, and document analysis. The findings reveal that land conflicts primarily stem from overlapping claims between customary land (ulayat) and investment concessions legitimized by state law. In the absence of meaningful access to formal legal mechanisms, the Malind community relies on customary deliberation, symbolic rituals, and clan origin narratives as mechanisms of conflict resolution and forms of counter-hegemonic legality. Drawing on legal pluralism, critical agrarian studies, and political ecology, this article argues that local wisdom should be understood not merely as cultural practice but as a form of non-state legality with political significance in defending indigenous living spaces. The study highlights the need for substantive recognition of customary law and indigenous territories as integral components of equitable agrarian governance and investment policy.